SISTEM INFORMASI MANAJEMEN ASET KATEGORI ELEKTRONIK MENGGUNAKAN METODE AGILE - Tranhuji Gumbara; M. Zakki Abdillah (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
Electronic asset management is important to increase operational efficiency and minimize the risk of loss or damage to goods that are company assets. Developed system for managing inventory data, maintenance and asset reporting. The development process follows the Agile stages, starting from gathering requirements through interviews and surveys with users. Next, the interface and system features are designed, as well as iterative testing to ensure the system meets user expectations. The result of this research is an information system that can manage electronic asset data effectively, increase information accuracy, and speed up the decision-making process. It is hoped that the implementation of this system can make a significant contribution to asset management in the organization and increase transparency and accountability in the use of resources.